Analisis Parameter Proses Atomisasi Sentrifugal Tipe Elektroda Berputar dan Karakterisasi Serbuk Hasil Atomisasi pada Material Baja Paduan: Parameters Analysis of Centrifugal Atomizing Process of Rotating Electrodes Type for Alloy Steel Materials and Characterization of Atomized Powder - Dr. Ir. Slameto Wiryolukito; Thomas Albatros (Jurnal Metalurgi dan Material Indonesia, 2019)
Small components that have complicated geometry and precise dimensions are suitable to be produced by using powder metallurgy method. In Indonesia, powder metallurgy is not well developed, one of the causes is dependence on imported powders. This study discusses the effect of various parameters of making metal powders using centrifugal atomization machines on the character of the powders produced. The research includes the improvement of atomization tools, powder making, milling process, followed by the characterization process to determine the powder morphology, powder size distribution, and compounds formed from the resulting powder. The process parameters tested in this study are the type of raw material, the anode's rotational speed, and the amount of electric current applied. The raw materials used are reinforced steel, AISI 202, and AISI 304. With variations in rotational speed 4000rpm, 6000rpm and 8000rpm. The increase in rotational speed will reduce the size of the powder, and increasingly make the powder shaped like a ball. The milling process effectively reduces the size of alloy steel with a reduction of up to 89% in the form of angular powder. The XRD results show that the reinforced steel powder produced by atomization produces Fe2O3 and FeO powder, while AISI 202 and AISI 304 produce Cr2MnO4 compounds.